Boosting the French Canadian Town: Municipal Government and Urban Growth in Quebec, 1850-1900 - Rudin, Ronald (Urban History Review / Revue d'histoire urbaine, 1982)
During the late nineteenth and early twentieth centuries, it was common for municipal governments across Canada to promote local economic growth through a variety of means. This process of promotion, which has come to be known as boosterism, has not generally been studied in Quebec, however. Owing to the continued power of the stereotype that saw French Canadians opposed to the use of government to promote economic development, most writers have simply concluded that boosterism was non-existent in Quebec. A closer analysis reveals an entirely different situation. In spite of limited resources municipal governments employed a variety of means to boost local development. These efforts were generally championed by local francophone businessmen who could see their own fortunes enhanced by the growth of their towns.